Small-Scale Event Sports TourisM as visitors' Attractions: The Case of Northern States in Malaysia - Abdul Wafi, Anisah; Lim, Khong Chiu; Ibrahim, Johan Afendi (2018)
Nowadays, many event organizers try to market their products b&ed on small-scale sports events which are usually organized and held in rural areas. This is due to the type of visitors ' who participate in such events because of several reasons. This study aims to examine the factors that influence visitors to visit these small-scale sports tourism events and whether such events can become a potential tourism product to attract visitors. A survey was undertaken in the Northern States of Malaysia. A set of questionnaires were distributed to the visitors of this small-scale sports tourism event. Data was collected among 468 visitors during the event in two northern states of Malaysia. Statistical Package for the Social Sciences (SPSS) used to analyse the data. Finding from this study has confirmed that small-scale event sports tourism can become one of the potential products for sports tourism besides mega sporting events. As many event organizers tend to focus on mega sporting events, organizing these small-scale sports tourism events can also generate positive economic benefits towards the community and indirectly to the state government.